Daylighting performance and glare calculation of a suspended particle device switchable glazing. (July 2016) - Ghosh, Aritra; Norton, Brian; Duffy, Aidan
Highlights: Voltage dependent transmission of a SPD glazing was recorded. Daylight illuminance for a SPD glazing has been monitored using a test cell. UDI, DGI, DF have been calculated for a SPD glazing "opaque", "transparent" states. Abstract: The daylighting performance of a suspended particle device (SPD) switchable glazing has been evaluated using an unfurnished outdoor south facing test cell with glazing to wall ratio of 1:8. Interior illuminance levels were determined using useful daylight illuminance level (UDI) for clear sunny, intermittent cloudy and overcast cloudy days. Daylight provided by an SPD and a same area of double-glazing were compared. Daylight glare indexes (DGIN ) and daylight factor (DF) were calculated for SPD "opaque" and "transparent" states. An electrically actuated suspended particle device switchable glazing with transparency that varied between 5% and 55% was found to control daylight glare.